Topical therapy with rhubarb navel plasters in patients with chronic constipation: Results from a prospective randomized multicenter study. (10th January 2021) - Wei, Lin; Luo, Yueming; Zhang, Xiaopei; Liu, Yangchen; Gasser, Martin; Tang, Fang; Ouyang, Wen-wei; Wei, Hengqiu; Lu, Shengzhen; Yang, Zhen; Waaga-Gasser, Ana Maria; Deng, Chong; et al.
Abstract: Ethnopharmacological relevance: Constipation is a functional gastrointestinal disorder and one of the most prevalent conditions encountered in primary care settings. Rhubarb navel dressings have been used for more than 2, 000 years in Chinese medicine to treat constipation. However, the effect of topical rhubarb administration has still not been well recognized and this strategy is not yet established as an evidence-based approach. Aim of the study : In this study, we performed a prospective multicentric randomized controlled trial to evaluate the efficacy and safety of rhubarb navel plasters for patients with chronic constipation. Materials and methods: A total of 374 patients from six teaching hospitals were prospectively included between 09/2016 and 10/2017 in the study based on Rome III criteria. All participants were randomly assigned (1:1) into verum/placebo group and given either Rheum officinale rhubarb powder or a placebo flour stick on the navel for 6 h/day/8 days. Primary outcome measures were the Cleveland Constipation Score (CCS) for the feces condition and Bristol Stool Scale (BSS) for stool consistency and 24 h defecation frequency. Results: The groups demonstrated no statistical differences in demographic data, clinical diagnoses and concomitant medication at baseline. In patients treated with the verum CCS was 5.61 (day 8, 95% CI 5.15–6.07) compared to 8.62 (95% CI 8.07–9.18) in placebo-treated controls ( P  < 0.001). The mean change of CCS at the end of treatment (day 8 versus [vs] day 0) was 6.04 in verum-treated vs 2.73 in placebo-treated controls ( P  < 0.001). Also 24 h defecation frequency (BSS) showed superior results (day 5: 0.84 vs 0.62, 95% CI 0.67–0.80, P  < 0.001; day 6: 0.82 vs 0.60, 95% CI 0.64–0.78, P  < 0.01 and day 8: 0.82 vs 0.60, 95% CI 0.64–0.78, P  < 0.01) and better BSS type classification during treatment than controls ( P  < 0.05). No significant differences in adverse events between both groups became obvious. Conclusion: Rhubarb navel plaster administration over an 8-day-treatment period resulted in significantly improved bowel function as demonstrated by the CCS, 24 h defecating frequency and BSS. Our results suggest that rhubarb navel plasters represent a feasible, safe and efficient application route for the treatment of patients suffering from chronic constipation. Graphical abstract: Image 1